An evaluation of Aggression Replacement Training: the impact of a multi-component, CBT-based intervention on the problem behaviours, pro-social skills and moral development of pupils in English secondary schools - Grimes, Samantha (2015)
Aggression Replacement Training (ART) is a 10-week, multi-component intervention based in cognitive behaviour therapy (CBT), which aims to improve social competence. It has been applied internationally as part of offender rehabilitation (NOMS, 2010). However, more recent research has focused upon its application in school-based settings. The aim of the current research is to investigate the efficacy of ART when implemented in the UK with an adolescent sample in mainstream school settings. These sessions were facilitated by newly-trained staff from the Educational Psychology Service (EPS). A quasi-experimental design was employed to evaluate this initial pilot of the programme in one Local Authority. 41 participants across six settings were allocated to intervention (N=23) and wait-list control (N=18) conditions. The Social Skills Improvement System-Rating Scales (SSIS-RS), a multi-source measure, was used to assess the group member’s problem behaviours and social skills, with data gathered from teachers, parents and pupils themselves. The Sociomoral Reflection Measure-Short Form (SRM-SF) was also completed by the participants to ascertain their moral reasoning maturity. Non-parametric statistical tests demonstrated no significant improvements in the intervention participant’s social skills or problem behaviours. However, their moral reasoning ability did increase significantly from pre to post-test, achieving a large effect size (r=-0.64), which was not reflected in the data from the control group. In contrast to the quantitative findings, supplementary qualitative data gathered from the facilitators and group members involved in the ART programme demonstrated that all felt the intervention had resulted in positive outcomes for the young people. Factors which may have contributed to the success of the programme were also provided, including organisational support and group composition. Possible explanations for these findings, including methodological considerations and comparison with previous research are discussed and the implications of these findings in future practice and in guiding further research suggested.